Climate change mitigation and food loss and waste reduction: Exploring the business case - Gromko, Duncan; Abdurasulova, Gulbahar (2018)
The carbon footprint of food loss and waste (FLW) is estimated to be up to 3.49 gigatons of carbon dioxide equivalent (gtCO2e), representing up to 6-10% of total anthropogenic greenhouse gas emissions. Reducing FLW can reduce the emission intensity of agricultural production. Moreover, many FLW reduction measures are profitable thanks to increased revenues. This study examines the business case for reducing FLW by examining three supply chains in detail: tomatoes in Nigeria, dairy in Kenya, and cereals in Tanzania. The cases reveal key strategies involving enabling environment, credit, business promotion that should inform other efforts to reduce FLW at scale. Additional research is needed to assess social justice and equity and to focus on cases that may directly benefit women.